Influence of Group Purchasing Organizations On Financial Situation Of SMEs - Grzegorz Zimon (Institute of Economic Research (IER), 2017)
Research background: SMEs often operate in markets where they compete with large companies. A fight for the customer, payment backlogs, problems with debt collection and new branches make management seek solutions that will influence positively on the situation of financial companies. Maintaining liquidity and generating income are the primary steps to build a competitive position and a progressive development of enterprises. One of the most popular methods that allows companies to do profitable business and increase their chances for safety is operation within group purchasing organizations. Currently in the market there are many different types of GPOs (Group Purchasing Organizations). The choice of the right one is a chance to improve their financial situation. Purpose of the article: This article presents functioning of enterprises within group purchasing organizations and their impact on financial situation of enterprises. In the article the classification of groups is done and there are shown the benefits that commercial enterprises operating in them gain. The article presents some obstacles to join specific group purchasing organizations and difficulties faced by companies operating in them. Methodology/methods: The studies will be carried out on the basis of 60 SMEs. These companies operate in five Polish GPOs. The groups were divided into branch and multi-branch ones. The study period covered the years 2013-2015. In order to analyze the impact of purchasing groups on the financial situation of enterprises there were used selected groups of financial ratios and a preliminary analysis of financial balance sheets and profit and loss account was conducted Findings: The analysis showed that the choice of an appropriate group purchasing organization has a large impact on financial situation of companies. Different opportunities can be offered by a sectoral purchasing group than the multi-sectoral one. Research has shown that better results relate to dynamics of revenues, costs, liquidity, profitability that gives the operation within the sectoral purchasing groups.
Keywords: A11; A14; B16; 330; group purchasing organization; finance; commercial enterprises